فاعلية الإعلام الموجه في تعزيز السلام الاجتماعي , دراسة حالة إذاعة السلام ,السودان الفترة (2013 - 2016 ) - البدوي احمد, د. جهاد احمد; حاج البشير, د. حافظ عثمان (Gezira Journal of Educational Sciences and Humanities; مجلد 18 عدد 2 (2021), 2022)
مستخلص استخدمت هذه الدراسة المنهج الوصفي لتقصي فاعلية الإعلام الموجه في تعزيز السلام الاجتماعي من خلال دراسة حالة إذاعة السلام. وذلك بإجراء دراسة ميدانية تطبيقية على مستمعي إذاعة السلام مستخدمة أداة الاستبيان لجمع البيانات. توصلت الدراسة إلى عدد من النتائج، أهمها أن الراديو وسيلة إعلامية تُحظى بتفضيل قطاع عريض من أفراد المجتمع.يتابع إذاعة السلام فئات مختلفة ومتنوعة من المجتمع باختلاف اعمارهم خاصة الشباب.وعملت إذاعة السلام علي تعزيز مفهوم الهوية الثقافية في المجتمع بشكل كبير، وذلك من خلال تغطية كافة أشكال التنوع الثقافي والاجتماعي والعرقي في جميع أنحاء السودان.أسهم مضمون البرامج الاجتماعية الموجه في إذاعة السلام أسهم بصورة واضحة في تعزيز السلم الاجتماعي، حيث يتم إعداد تلك البرامج بمنهجية تتناسب ومفاهيم السلام الاجتماعي. وأكدت الدراسة دور الإذاعة في تثبيت السلم الاجتماعي من خلال برامجها ذات الطبيعة التفاعلية والتي تحمل هموم المجتمع، وتعرف بمكوناته لبناء ثقافة السلام وتعزيز السلام الاجتماعي.أوصت الدراسة بالاهتمام ودعم وسائل الإعلام التي تساهم في تعزيز السلام الاجتماعي، التعريف بالثقافات واللهجات واللغات المحلية من خلال برامج خاصة، والتعاون وتبادل الخبرات مع الجهات ذات الاهتمام بمجال السلام الاجتماعي داخل وخارج البلاد بما يعود بالفائدة على المستمعين والمجتمع. Abstract This study used he descriptive method to investigate the effectiveness of the oriented media in enhancement of social peace through the case study of Radio Peace. A field survey among peace radio audience using a questionnaire as a tool of data collection tool was carried out. The study came out with a number of findings, the most important of which is that radio is a media that has a large audience. Radio Peace audience are from different age groups, particularly, young people. Radio Peace worked to promote the concept of cultural identity in the society through introducing different aspects of cultural, social and ethnic diversity around the country. The theme of oriented social programs in peace radio had remarkably contributed to promotion of social peace, as the programs preparation consider concepts of social peace. The study confirmed the role of radio in settling of social peace through programs of interactive nature that address the concerns of the community, and recognize its components to build a culture of peace and promotion of social peace.The study recommended the cooperation and exchange of experiences with the organizations concerned with social peace inside and outside the country for the benefit of audience and the society, consideration and support of mass media that contribute to promotion of social peace, identification of local cultures, dialects, and languages, through special programs.